Research on technology of improving top-coal recovery in longwall top-coal caving mining based on BBR system - Wang Jiachen; Zhang Jinwang; Chen Yi (矿业科学学报, 2016)
The optimization of drawing parameters is one of the major ways to improve top-coal recovery in longwall top-coal caving mining.Based on the BBR system，the drawing mechanism of loosen top-coal in mutil-openings and partially reverse drawing techniques were analyzed by loose top-coal drawing experiments and distinct element numerical calculations.The results show that the top-coal recovery ratio in mutil-openings condition is larger than that in single-opening condition.The increased volume comes from the middle and upper parts of the top-coal above the central face.With the increasing of opening length，the volume of drawing body increases linearly and the rock mixed position in drawing body moves to directly above the opening；the shape of the boundary of the top coal appears the bulging characteristic toward the goaf gradually.The partially reverse drawing technique increases the top-coal recovery ratio in the lower end of the face by 13.98% compared to normal drawing technique.The shape of the boundary of the top-coal near the junction of reversed segment and normal segment is beneficial to the development of drawing body，which decreases the residual coal in the goaf.With increasing reversed segment’s length，the growth rate of the drawing volume in reversed segment decreases after an initial increasing phase.The top-coal recovery ratios in both the middle and the lower parts of the face are increased by using the partially reverse drawing technique with double-openings.